Great Lakes Accelerated Innovation Delivery Initiative Rapid Delivery Hub in Burundi - Part 2 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
AIDI Great Lakes Region is disseminating agronomic technologies in Burundi to improve the livelihood of smallholder farmers. In this video, a farmer in Kirundo Province shares positive feedback from the field-level experience after implementing agronomic practices recommended under AIDI framework.